Physical quality assessment of selected made in Nigeria synthetic surfactants for surface activity in Bali, Taraba State, Nigeria - MATTHEW ONYEMA AGU; Umar Kyakyaidi; Collins Chibuzor Odidika; Agha Inya Inya (African Scientific Reports)
The properties of high-quality soap is determined by its cleansing, foam formation, surface tension, emulsion capacity, pH, etc. To produce a generally better product, soap manufacturing companies take these properties into account during production which necessitated the physical assessment properties of some selected made-in-Nigeria synthetic surfactant for surface activity. The samples were evaluated based on tests for saponins, foam formation and stability, emulsion formation/capacity, surface tension, and pH at different concentrations. The percentage of each of the synthetic surfactants (Ariel=DA, Bonus=DB, Good mama=DG, Sunlight=DS and Zip=DZ) concerning foam formation at five minutes and stability after 30 minutes were as follows; DZ(6.7) > DS(6.3) > DG(5.3) > DA(4.2) > DB(4.1) and DZ(2.6) > DG(1.9) > DA(1.1)/DS(1.1) > DB(1.0) in cm, respectively. The study of the emulsion formation/capacity of the different samples at different concentrations in terms of creamy behaviour was observed as DS > DZ > DA > DG > DB. All the samples studied showed a good reduction in surface tension. At 2g and 10g of the different samples, the following results were obtained: DS(2.87), DZ(20.25), DB(21.55), DA(21.65), DG(21.85) Nm-1 and DS(22.45), DZ(22.25), DB(22.45), DA(26.65), DG(22.65) N/m, respectively. The result of the pH values of the different samples varied within the range of 10.80 to 10.91 as moderately weak base with an increase in concentration. Detergents studied conform to the minimum quality examinations but regular assessment check should be carried out by enforcement/regulatory agencies to ensure quality of detergents produced in the country meets the minimum required standard.